Infratentorial onset of progressive multifocal leukoencephalopathy in a patient with systematic lupus erythematosus complicated with lymphoma: a case report. (3rd April 2021) - Sakuraba, Mita; Watanabe, Shinji; Nishiyama, Yasuhiro; Takahashi, Kenta; Nakamichi, Kazuo; Suzuki, Mikito; Nawata, Takashi; Komai, Kota; Gono, Takahisa; Takeno, Mitsuhiro; Suzuki, Tadaki; Kimura, Kazumi; et al.
Abstract: Progressive multifocal leukoencephalopathy (PML) is a rare opportunistic infection of the central nervous system caused by reactivation of JC virus (JCV). Typical PML shows confluent, bilateral but asymmetric, subcortical lesions in the supratentorial white matter on magnetic resonance imaging (MRI). We report here a 50-year-old woman with systemic lupus erythematosus complicated with lymphoma who developed PML with atypical brain MRI findings limited to the infratentorial area at presentation. She presented with numbness on the right side of the face, including her tongue, clumsiness of the right hand, and gait disturbance, after completion of remission induction therapy for lymphoma, including rituximab. Brain MRI demonstrated a solitary lesion limited to the cerebellum and brainstem, but a definitive diagnosis could not be made from cerebrospinal fluid study or tentative histologic evaluation of brain biopsy specimens. Despite methylprednisolone pulse therapy, her neurological deficits progressively worsened. One month later, in-depth analysis of her cerebrospinal fluid and brain biopsy specimens confirmed the presence of JCV. Eventually, the localised unilateral crescent-shaped cerebellar lesions on MRI expanded to the contralateral cerebellum, middle cerebellar hemisphere, pons, and midbrain and finally developed multifocal invasion into the white matter of the cerebral hemispheres. Our case suggests that PML could first present with a solitary infratentorial lesion in immunocompromised patients.